2006
DOI: 10.1017/s0265021506001074
|View full text |Cite
|
Sign up to set email alerts
|

High volume and low concentration of anaesthetic solution in the perivascular interscalene sheath determines qualityof block and incidence of complications

Abstract: The lower concentration of the anaesthetic solution avoids complications while increased volume provides good analgesic cover. The combination of the Winnie interscalene plexus block and the Pippa proximal cranial needle approach should contribute to fill up the scalene sheath overcoming the septa obstacles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…This more frequent rate may be explained by differences in the local anesthetic volume (20 ml vs 0.4 ml/kg) or by slight methodological differences in the assessment of blockade [4,14,15]. Pippa et al [16] concluded that a lower concentration of anesthetic solution avoids complications, while an increased volume provides good analgesic cover. In our study, the rate of complete motor blockade between groups differs to that reported by Cox et al Cox et al [4] found that 68% of patients had a ''satisfactory block'' after a supraclavicular brachial plexus Values are numbers of patients (n) and percentages (%).…”
Section: Discussionmentioning
confidence: 99%
“…This more frequent rate may be explained by differences in the local anesthetic volume (20 ml vs 0.4 ml/kg) or by slight methodological differences in the assessment of blockade [4,14,15]. Pippa et al [16] concluded that a lower concentration of anesthetic solution avoids complications, while an increased volume provides good analgesic cover. In our study, the rate of complete motor blockade between groups differs to that reported by Cox et al Cox et al [4] found that 68% of patients had a ''satisfactory block'' after a supraclavicular brachial plexus Values are numbers of patients (n) and percentages (%).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in local anaesthetic concentration was also an option. This is supported by research showing a reduction in rates of ipsilateral phrenic nerve palsy from 27% to 0% with equivalent doses, but a reduction of local anaesthetic concentration of a ropivacine/lidocaine mixture [5].…”
Section: Discussionmentioning
confidence: 80%
“…O tempo de médio de latência, considerando todos os pacientes do estudo, foi de 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) minutos. Quando considerado apenas os pacientes que receberam bloqueios com a concentração de 0,25% (a concentração mais pró-xima da CME90), o tempo médio de latência foi de 20 (15)(16)(17)(18)(19)(20)(21)(22)15) minutos. Os tempos médios de latência para cada concentração analisada estão resumidos na tabela 4.…”
Section: Resultsunclassified
“…Pippa et al demonstraram que o uso de altas concentrações de anestésico local para o bloqueio do plexo braquial por via interescalênica está associado com um maior número de complicações, como paralisia do nervo frênico e hipotensão. 19 Além disso, estudos in vitro demonstraram que o uso de anestésico local está associado a efeitos citotóxicos, entre eles, indução de apoptose em células de Schwann, lesão mitocondrial, ativação de caspase e aumento de cálcio citoplasmático. Entretanto, todos esses efeitos estavam relacionados ao tempo de exposição e à maior concentração do fármaco utilizado, o que, teoricamente, sugere uma maior segurança quando se utiliza concentrações menores de anestésico local.…”
Section: Discussionunclassified